V.N. TATISHCHEV’S BUSINESS LETTERS IN THE GENRE ASPECT (BASED ON THE DOCUMENTS OF THE NATIONAL ARCHIVE OF THE REPUBLIC OF KALMYKIA) - Elena M. Sheptukhina (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
Business letters written in the 18th century are considered in the article within the independent epistolary genre. The material for the analysis was comprised of the official letters written by Privy Councillor V.N. Tatishchev during his governorship in Astrakhan and heading the Kalmyk Commission at the Board of Foreign Affairs. The documents are stored in the National Archive of the Republic of Kalmykia. The study was conducted using the model of document genre that combines multi-level coordinated parameters, such as: “function”, “addresser”, “addressee”, “nature of the information transmitted”, “structure”, “modality”, “space”, “time”. The linguistic means of their realization are revealed. Being determined by the functions of the writing and the status relations of the addresser and the addressee, the variability of these means is noted and described. The results of the analysis have enabled the author to determine that business letters provide the addresser with the opportunity to carry out communication in different directions: vertical (with higher or lower addressees) and horizontal (with the addressees who have equal status with the addresser). They perform the informing and regulating functions, thus implementing the corresponding modality, and have a similar structure with a stable set of elements and the order of their sequence in the text. The genre specificity of the documents under study is manifested in the absence of self-nomination and mandatory reference to the addresser, in the use of a welcome address as a means of expressing the “addressee” properties, and the presence of optional elements.